MICROSOFT VISUAL BASIC 6.0 APPLICATION FOR PRESENTATION OF INFORMATION AND VALUE ACADEMIC BIODATA INFORMATION ON STUDENT SMAN 78 JAKARTA - Leo Fungirawati; Eko Hadiyanto, Ssi, MMSI Eko Hadiyanto, Ssi, MMSI (Jurnal Sistem Informasi, 2006)
To support teaching and learning activities in order to run smoothly at a grammar school it is necessary to deal with all matters of business stationery - writing, covering services, correspondence, filing, financial, recording student data, and so forth. But in general upper secondary school in Jakarta, the process of entry, storage, updating, and searching student data is still done manually.This also happened in SMAN 78 Jakarta, with the number of students and alumni are a lot of the manual method is considered less efficient, especially in storage by requiring the filing cabinet and finding a place large enough student data which takes a relatively long time. To the authors to design and create applications that can simplify the process of entry, storage, updating and searching student data. The application program is created, using the software Microsoft Visual Basic 6.0, with the applications, administrators simply type the NIS or the student's name or nickname if you want to find and update the student data. Similarly with the presentation of information biodata and academic values desired by the requesting student information can be processed quickly.